1987
DOI: 10.1111/j.1464-410x.1987.tb04941.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Carcinoma: a Ten‐year Review 1971–1980

Abstract: A review of 72 patients who underwent nephrectomy for renal carcinoma between 1971 and 1980 is presented. All survivors were followed for a minimum of 5 years. The clinical features, type of operation and pathological findings were analysed for their influence on survival. Patients with stage 1 to 3 disease had a 65% 5-year survival rate, whereas all patients with stage 4 disease were dead within 2 years. The presence of malaise had a highly significant adverse influence on survival (P = 0.0014).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…These results are compatible with other reports and suggest that there is no delay in the presentation or diagnosis of renal cancer in our patients similar to that seen with other urological cancers in Saudi Arabia. [13][14][15]17 Only 6% of the patients presented in Stage III, a much smaller but variable percentage in comparison to other studies. The incidence of patients with Stage III disease varies greatly in different reports and usually follows the referral pattern to tertiary centers that deal with these patients.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…These results are compatible with other reports and suggest that there is no delay in the presentation or diagnosis of renal cancer in our patients similar to that seen with other urological cancers in Saudi Arabia. [13][14][15]17 Only 6% of the patients presented in Stage III, a much smaller but variable percentage in comparison to other studies. The incidence of patients with Stage III disease varies greatly in different reports and usually follows the referral pattern to tertiary centers that deal with these patients.…”
Section: Discussionmentioning
confidence: 57%
“…A male-to-female ratio of 2-3:1 is reported in many series. [13][14][15] Jamal et al reported on a group of 30 patients with renal neoplasia; among those, there were 21 Saudi patients with a M:F ratio of 4:1. 16 This was not our observation, where the ratio of 1.3:1 suggests a higher occurrence in Saudi females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations